Management of Meconium Ileus: 5 years' experience at Dhaka Shishu (Children) Hospital - Ferdous, Kazi Md Noor ul; Hasan, Md Samiul; Kabir, Kh Ahsanul; Islam, M Kabirul; Banu, Tahmina (Northern International Medical College Journal, 2019)
Background : Meconium ileus (MI) is one of the common cause of intestinal obstruction in neonate. It can be present with various complications (about 50%) like volvulus, atresia, and gangrene of the gut, perforation and meconium cyst. Objective : This study aimed to compare various surgical procedures used in the treatment of meconium ileus and to assess their efficacy regarding survival and complications in our center. Methods : This retrospective study was done to all cases of meconium ileus admitted in the Department of neonatal surgery of Dhaka Shishu (Children) Hospital during the past 5 years (2011 to2016). The medical records of all patients with meconium ileus were studied. The surgical procedures were Mikulicz procedure, Bishop-Koop procedure done in case of complicated cases and Mikulicz procedure, Bishop-Koop and T tube ileostomy done in uncomplicated cases. Outcomes were compared between complicated and uncomplicated group and between the surgical procedures. Results : Total patients were 224. Among them 8 were excluded due to incomplete data. The mean age was 3.23 days. Twenty four neonates were preterm. Fifty-two percent were uncomplicatedMI and 48.15% were complicated. Among 112 uncomplicated cases, Mikulicz procedure done in 33 cases, Bishop-Koop procedure done in 37 cases and rest were treated by T tube ileostomy procedures. Among 104 cases of complicated meconium ileus, Mikulicz procedure done in 75 cases and 42 cases were treated by Bishop-Koop stoma. Predominant complications in Mikulicz procedures were high output fistula (67.6%), sepsis (34.84%) and skin excoriation (58.33%), while in Bishop-Koop procedure were sepsis (59.25%), anastomotic leak and reoperation (25.75%). In T tube ileostomy, complications were intra-peritoneal leak with reoperation and sepsis (9.52%). Twenty five (11.6%) stoma prolapse were found in Mikulicz ileostomy. The overall mortality of meconium ileus was 36.6%, in simple MI 23 out of 112 and in complicated MI 56 out of 104. This difference was significant. Conclusion : Considering the study result we concluded that complications occur more frequently in Mikulicz procedure and it is significantly associated with mortality, Bishop- Koop ileostomy can be considered but anastomotic leak is still an important complication of this procedure. In uncomplicated cases T tube ileostomy found as the best option. Northern International Medical College Journal Vol.10(1) Jul 2018: 326-329